Compliance and financial crime risk in banks : a practitioners guide - Velez, Sophia Beckett (Emerald Publishing Limited, 2024)
US and global banking regulators have enforced compliance laws to minimise money laundering, terrorist funding, human trafficking, fraudulent banking activities, and bad mortgage loans that expose banks to significant risks and losses. However, many banks have complained of over-regulation. 'Compliance and Financial Crime Risk in Banks: A Practitioners Guide' investigates anti-money laundering standards, counter-terrorist financing measures that cover the Bank Secrecy Act laws, and control activities designed to mitigate breaches, such as 'prevent, detect, and monitor'. A focus group of ten senior banking finance experts was convened to build consensus on compliance practices that senior bank managers can implement to be effective in reducing losses in banks/bank holding companies. The result is the following consensus: a) Maintenance of effective and independent compliance, consistent with the organisational objectives b) Clear definition of data sources for compliance analytics c) Compliance monitoring d) Reporting activities to upper management e) Top leadership must champion their code of ethics f) Understanding the regulatory compliance activities that are effective Author Sophia Beckett Velez offers an original contribution to the field of banking that Undergraduates, Master's, Ph.D. students, academics, and researchers can use to gain a deeper understanding of compliance, and AML risks in banks, and the use of effective management practices.